Complete Chloroplast Genome Sequencing and Phylogenetic Analysis of Two Dracocephalum Plants. (30th December 2020) - Yao, Junjun; Zhao, Fangyu; Xu, Yuanjiang; Zhao, Kaihui; Quan, Hong; Su, Yanjie; Hao, Peiyu; Liu, Jiang; Yu, Benxia; Yao, Min; Ma, Xiaojing; Liao, Zhihua; et al.
Abstract : Dracocephalum tanguticum and Dracocephalum moldavica are important herbs from Lamiaceae and have great medicinal value. We used the Illumina sequencing technology to sequence the complete chloroplast genome of D. tanguticum and D. moldavica and then conducted de novo assembly. The two chloroplast genomes have a typical quadripartite structure, with the gene's lengths of 82, 221 bp and 81, 450 bp, large single-copy region's (LSC) lengths of 82, 221 bp and 81, 450 bp, and small single-copy region's (SSC) lengths of 17, 363 bp and 17, 066 bp, inverted repeat region's (IR) lengths of 51, 370 bp and 51, 352 bp, respectively. The GC content of the two chloroplast genomes was 37.80% and 37.83%, respectively. The chloroplast genomes of the two plants encode 133 and 132 genes, respectively, among which there are 88 and 87 protein-coding genes, respectively, as well as 37 tRNA genes and 8 rRNA genes. Among them, the rps2 gene is unique to D. tanguticum, which is not found in D. moldavica . Through SSR analysis, we also found 6 mutation hotspot regions, which can be used as molecular markers for taxonomic studies. Phylogenetic analysis showed that Dracocephalum was more closely related to Mentha .